Anti-angiogenic therapeutic strategies in hereditary hemorrhagic telangiectasia - Ardelean, Daniela S.; Letarte, Michelle (Frontiers in Genetics, 2015)
Hereditary hemorrhagic telangiectasia (HHT) is an autosomal dominant vascular dysplastic disorder, characterized by recurrent nosebleeds (epistaxis), multiple telangiectases and arteriovenous malformations (AVMs) in major organs. Mutations in Endoglin (ENG or CD105) and Activin receptor-like kinase 1 (ACVRL1 or ALK1) genes of the TGF-β superfamily receptors are responsible for HHT1 and HHT2 respectively and account for the majority of HHT cases. Haploinsufficiency in ENG and ALK1 is recognized at the underlying cause of HHT. However, the mechanisms responsible for the predisposition to and generation of AVMs, the hallmark of this disease, are poorly understood. Recent data suggest that dysregulated angiogenesis contributes to the pathogenesis of HHT and that the vascular endothelial growth factor, VEGF, may be implicated in this disease, by modulating the angiogenic balance in the affected tissues. Hence, anti-angiogenic therapies that target the abnormal vessels and restore the angiogenic balance are candidates for treatment of HHT. Here we review the experimental evidence for dysregulated angiogenesis in HHT, the anti-angiogenic therapeutic strategies used in animal models and some patients with HHT and the potential benefit of the anti-angiogenic treatment for ameliorating this severe, progressive vascular disease.